Answer:
x=1 so it has a solution
Explanation:
implifying
11 + -2x + 4 = 8 + 5x
Reorder the terms:
11 + 4 + -2x = 8 + 5x
Combine like terms: 11 + 4 = 15
15 + -2x = 8 + 5x
Solving
15 + -2x = 8 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
15 + -2x + -5x = 8 + 5x + -5x
Combine like terms: -2x + -5x = -7x
15 + -7x = 8 + 5x + -5x
Combine like terms: 5x + -5x = 0
15 + -7x = 8 + 0
15 + -7x = 8
Add '-15' to each side of the equation.
15 + -15 + -7x = 8 + -15
Combine like terms: 15 + -15 = 0
0 + -7x = 8 + -15
-7x = 8 + -15
Combine like terms: 8 + -15 = -7
-7x = -7
Divide each side by '-7'.
x = 1
Simplifying
x = 1